Media Puzzle Angka dalam Pemahaman Konsep Berhitung pada Siswa Kelas II SDN 5 Tanjung Lago - Mutia Mawardah; Tia Rizkia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service program aims to assist second-grade students at SDN 5 Tanjung Lago in understanding basic numeracy concepts. The method applied is Learning through Play, using Number Puzzle media as an instructional tool. The results of the community service activity indicate that the implementation of this media has a positive impact on both the learning process and students’ mathematics learning outcomes. Through concrete and enjoyable learning activities, students are able to more easily comprehend basic arithmetic operations. Furthermore, the use of Number Puzzles has been proven to increase students’ motivation and interest in learning. A learning atmosphere designed in the form of games, combined with the provision of rewards, encourages students to be more active, diligent, and enthusiastic in participating in learning activities.